CORRELATION BETWEEN MATHEMATICS ANXIETY AND ATTITUDE TOWARDS ACCOUNTING EDUCATION IN COLLEGES OF EDUCATION IN ENUGU STATE - Nezeani, Aishatu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The concept of mathematics anxiety has attracted overwhelming research attention in recent years. However, little is known about the association between math-related anxiousness and students' attitudes in the accounting domain. The present paper examined the relationship between mathematics anxiety and attitudes towards accounting among undergraduates in colleges of education in Enugu state. One hundred and forty-two (n=142) male and female undergraduates in the business education departments in two public colleges of education in Enugu state participated in the survey. The respondents completed a self-report measure of the mathematics anxiety and accounting attitudes scale. Pearson's product-moment correlation was performed to determine the correlation between mathematics anxiety and attitudes towards accounting. The result revealed a statistically significant, moderate positive correlation between mathematics anxiety and attitudes towards accounting, r (140) = .41, p < .001. Most importantly, observation of the R2 revealed that mathematics anxiety explained about 116% of the variation in students' attitudes towards accounting. The result offers valuable data for the development of accounting education in colleges of education in Nigeria.